PENGARUH ASET PRODUKTIF, PEMBIAYAAN BERMASALAH DAN LIKUIDITAS TERHADAP PROFITABILITAS DENGAN KECUKUPAN MODAL SEBAGAI VARIABEL MODERASI - Fadilah, Elsa; Suryani, Suryani; Raya, Fitri (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2023)
Increased productive assets, healthy FDR, and suppressed NPFs do not increase the Bank's profitability. The purpose of this study is to test and analyze the effect of productive assets, NPF, and FDR on profitability with CAR as a moderation variable. The data collection method is carried out by accessing financial statements through the official website. The data is processed with SPSS 25 tools. The analysis used includes classical assumption tests, multiple linear regression tests and MRA tests. Productive assets, NPF and FDR have a partial effect on profitability. Similar results are obtained with the f test which states that productive assets, NPF and FDR have a simultaneous effect on profitability. The moderation test interprets that CAR is unable to moderate the effect of productive assets, NPF and FDR on profitability.